The evaluation of investment projects within the territory of development - Griškevičiūtė-Gečienė, Aušrinė (Transport, 2010)
Sustainable development is the most researchable sphere of many experts in urbanistics, architecture, transport, environment and economics in Lithuania. Every period of time has specific problems and solutions to solve them. The present days have increased the level of automobilization and growing traffic in cities has become the main task for sustainable development. State‐wide improvement and development of transport infrastructure relate to the level of assigned investments that depend on State transport policy and existing opportunities. Comparing to several EU member states, the procedures of evaluating data on transport infrastructure projects evolved in parallel with the EU‐financed projects. Therefore, it could be stated that this area is not falling behind. The analysis of evaluation methods in Lithuania and foreign countries showed that there were no standardized and united methods for evaluating projects on urban system infrastructure. During the last decade, investment projects in cooperation with the State were evaluated using complex analysis in Lithuania. Cost‐benefit analysis was and is still being used for evaluating the EU‐financed projects. Multicriteria analysis is often carried out in the EU and other countries to evaluate the financial feasibility of transport infrastructure and takes its first steps in Lithuania.First published online: 27 Oct 2010